Prevalence of theileriosis and babesiosis in cattle in Sirajganj district of Bangladesh (Research in Agriculture Livestock and Fisheries, 2015)
A study was conducted to investigate the prevalence of theileriosis and babesiosis in cattle in Sirajganj district of Bangladesh during the period of December 2013 to November 2014. During one year study period a total of 395 cattle were examined, 23 and 8 were found to be infected with Theileria spp. and Babesia spp., respectively. On Geimsa stained blood smear examination, it was observed that the overall prevalence of theileriosis and babesiosis in cattle were recorded as 5.82% and 2.27% respectively. The effect of age, sex, breed and season was observed in cattle during this study. The highest prevalence of theileriosis (7.25%) and babesiosis (3.10%) was reported in the older cattle (>3 years of age) and the higher prevalence was observed in female (6.66% and 2.59%, respectively) than male (4.0% and 1.60% respectively). All crossbred cattle was showed higher prevalence than local cattle. The prevalence of theileriosis was noticed as the highest in the rainy season (6.25%) in relation to summer (5.83%) and winter (5.05%) season. But the prevalence of babesiosis was ranked the highest in summer season (2.50%) followed in rainy (2.27%) and winter (2.02%) season that was insignificant. From the study it was evident that cattle were infected with the organisms and caused a heavy economic loss which will assist to take necessary preventive measurements.Res. Agric., Livest. Fish.2(1): 79-86, April 2015